Fine Fraction of Iron Ore Tailings as Mineral Addition in Self-Compacting Mixtures - Cipriano, Marcelly Pires de Sousa Ramos (2024)
Global mining generates approximately 60 billion tons of waste each year, mostly stored in tailings dams, causing environmental damage and threatening nearby communities. To address this issue in alignment with circular economy principles, this study explored using the fine fraction of iron ore tailings (<0.075 mm) as a mineral addition for producing self-compacting mixtures, which require a substantial fines content. The study assessed mortars with 10%, 20%, and 30% mining filler (MF) replacing cement, comparing them to equivalent limestone filler (LF) mixtures and a reference without additives. The properties of the additions were assessed using X-ray diffraction, X-ray fluorescence, laser granulometry, scanning electron microscopy, methylene blue test, R3 test, and furnace-based gravimetry test. Fresh state analysis on mortars included specific gravity, flow table, and mini V-funnel tests. In the hardened state, tests covered compressive and flexural strength, ultrasonic pulse velocity, porosity, scanning electron microscopy, and mercury intrusion porosimetry (MIP). Isothermal calorimetry was also conducted on pastes to evaluate the cement hydration kinetics. It was found that the additions anticipated the induction period compared to the reference, with minimal impact on its duration. Otherwise, the heat release was most affected, with LF increasing it by 8%, 14%, and 17% at 10%, 20%, and 30% content, and MF rising it by 9%, 13%, and 22%. Mortars with additions showed improved spreading compared to the reference, with MF enhancing it by approximately 8%, 10%, and 15% at 10%, 20%, and 30% replacements, surpassing limestone filler at the same levels. MF, at 10%, 20%, and 30% replacements, reduced V-funnel times by around 30%, 31%, and 27% respectively compared to LF. At 28 days, mortars with MF showed around 6%, 4%, and 2% higher compressive strength than mLF at 10%, 20%, and 30% substitutions respectively. The mortar with 20% of MF incorporation had a cement index almost 13% lower than the reference mixture, implying a reduction of 65 kg of cement and the incorporation of 133 kg of tailing for a mortar with a strength of 50 MPa. MIP results showed that this same mixture had a pore volume >200 nm 50% smaller than that with 20% of LF, with a slightly lower total porosity. Overall, the use of the fine fraction of iron ore tailings as mineral addition in self-compacting mixtures is feasible for contents up to 30% and environmentally advantageous compared to the use of LF.